(untitled) (Journal of the College of Basic Education, 2023)
This study is a trail to know if the genes controlling some of heavy metals resistance ( lead, zinc, cadmium, cromium) in two types of pathogenic bacteria (P .aeruginosa) as gram negative bacteria and ( S. aureus ) as gram positive bacteria, present on the β-lactamase plasmid. Ten isolates of each bacterial types which produced β-lactamase enzyme, were cultivated in the presence of acridine orange. The growing in the presence of acridine orange resulted in loss of the β-lactamase genes in S. aureus and P. aeruginosa, and loss of the heavy metals resistance in S. aureus, while the resistance of P. aeruginosa against heavy metals still without any change. The results indicated that the genes for heavy metals resistance existed on the β-lactamase plasmid in S. aureus only, while in P. aeruginosa the genes that controlling heavy metals resistance were not found on β-lactamase plasmid.